Liminal strategies and the development of contemporary Ukrainian dramaturgy - Bortnik, Zhanna (Research Journal in Advanced Humanities, 2023)
This article explores the potential integration of liminal strategies into literary studies research, focusing on the stages of development in contemporary Ukrainian dramaturgy. The purpose of this study is to examine how the application of liminal strategies can enhance literary studies research, specifically within the context of contemporary Ukrainian dramaturgy. The methodology employed involves an analysis of various works and critical perspectives in the field, with a particular emphasis on identifying and understanding the liminal aspects and transitions present in the development of Ukrainian drama. The accent is made on the conceptual framework of "rites of passage" by A. van Gennep and V. Turner, any innovations in an individual's life and society require the navigation of three stages of transition – separation, liminality, and incorporation. Findings from this research indicate that integrating liminal strategies into literary studies research offers valuable insights and a richer understanding of the dynamics and transformations within contemporary Ukrainian dramaturgy. By examining the liminal phases of separation and incorporation in the works of Ukrainian playwrights, this study sheds light on the intricate processes of transition and the social and cultural implications associated with them. The practical implications of this research lie in the potential for scholars and researchers to employ liminal strategies as a conceptual framework for studying other literary traditions and exploring the transformative nature of artistic expression. This study contributes to expanding the methodological toolkit in literary studies, encouraging a deeper engagement with the liminal dimensions of literary works and their socio-cultural significance.